Superstition in all ages - Holbach, Paul Henri Thiry, baron d', 1723-1789; Voltaire, 1694-1778; Knoop, Anna, -1889; Meslier, Jean, 1664-1729 (Salt Lake City, UT : Project Gutenberg, 2006)
"Superstition in All Ages" by Baron d' Paul Henri Thiry Holbach is a philosophical treatise written in the early 18th century. The work critically examines the origins and implications of superstition and religious dogmas through a historical and rational lens. It reflects the author's conviction that superstitions arise from ignorance and fear, and it argues for a rational inquiry into the beliefs that govern human behavior. The beginning of the text introduces Jean Meslier, a Roman Catholic priest who renounced religion after decades of service and left behind a manuscript arguing against religious dogmas, titled "Common Sense." The opening details Meslier's life, his pious actions, and the conflicts he faced with church authorities, establishing the foundation of his philosophical views. It highlights his intent to expose the contradictions of theology and the irrationality of faith, setting the stage for a critique of superstitions that persist throughout history. (This is an automatically generated summary.)
Release date is 2006-01-25
Produced by Gary Klein; HTML version by David Widger
Keywords: Atheism